Grace in Movement, Meaning in Craft: Penguatan Pendidikan Karakter Anak dan Remaja melalui Seni dan Budaya Lokal Papua di PAR Jemaat Immanuel Boswezen Sorong - Sherly Gaspersz; I Dewa Ayu Nyoman Utari Sastrani; Christin Sasauw; Antonius Demon Tupen; Diana Nova Aronggear; Marlin Ruth Korwa; Julius Kristian Masan (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Strengthening character education for children and adolescents has become urgent amid widespread moral degradation, low social empathy, and the influence of popular culture that does not support the formation of noble values, especially in the Southwest Papua region. This community service activity was carried out at the Immanuel Boswezen Sorong with the aim of instilling character values through an approach combining art and local Papua culture. The method used was Project-Based Learning (PjBL), with project activities such as traditional Papua dance, crown making, and bead bracelet crafting. The activity involved 20 participants aged 3–15 years. The results showed improvements in responsibility, cooperation, confidence in public speaking, and a sense of love for local culture. Eighty percent of participants showed a change in attitude, 85% understood cultural symbols, and 100% were able to complete their projects. This programme had a positive social and cultural impact and opened up opportunities for the formation of a sustainable cultural community. The arts and culture approach proved to be an effective strategy for contextual character education in religious communities.